Microbially produced glucagon-like peptide 1 improves glucose tolerance in mice - Tulika Arora; Udo Wegmann; Anup Bobhate; Ying Shiuan Lee; Thomas U. Greiner; Daniel J. Drucker; Arjan Narbad; Fredrik Bäckhed (Elsevier, 2016)
Objective: The enteroendocrine hormone glucagon-like peptide 1 (GLP-1) is an attractive anti-diabetic therapy. Here, we generated a recombinant Lactococcus lactis strain genetically modified to produce GLP-1 and investigated its ability to improve glucose tolerance in mice on chow or high-fat diet (HFD). Methods: We transformed L. lactis FI5876 with either empty vector (pUK200) or murine GLP-1 expression vector to generate LL-UK200 and LL-GLP1, respectively, and determined their potential to induce insulin secretion by incubating primary islets from wild-type (WT) and GLP-1 receptor knockout (GLP1R-KO) mice with culture supernatant of these strains. In addition, we administered these strains to mice on chow or HFD. At the end of the study period, we measured plasma GLP-1 levels, performed intraperitoneal glucose tolerance and insulin tolerance tests, and determined hepatic expression of the gluconeogenic genes G6pc and Pepck. Results: Insulin release from primary islets of WT but not GLP1R-KO mice was higher following incubation with culture supernatant from LL-GLP1 compared with LL-UK200. In mice on chow, supplementation with LL-GLP1 versus LL-UK200 promoted increased vena porta levels of GLP-1 in both WT and GLP1R-KO mice; however, LL-GLP1 promoted improved glucose tolerance in WT but not in GLP1R-KO mice, indicating a requirement for the GLP-1 receptor. In mice on HFD and thus with impaired glucose tolerance, supplementation with LL-GLP1 versus LL-UK200 promoted a pronounced improvement in glucose tolerance together with increased insulin levels. Supplementation with LL-GLP1 versus LL-UK200 did not affect insulin tolerance but resulted in reduced expression of G6pc in both chow and HFD-fed mice. Conclusions: The L. lactis strain genetically modified to produce GLP-1 is capable of stimulating insulin secretion from islets and improving glucose tolerance in mice. Keywords: Lactococcus lactis, Glucose tolerance, Recombinant bacteria, GLP-1